2014
DOI: 10.1149/06404.0135ecst
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Structure in Thin Films

Abstract: Room Temperature Ionic liquids present an exciting opportunity to examine surface confined thin fluid films and extended interfacial systems that may prove useful for electrochemical applications. This work explores the behavior of thin (1-5000 nm) films and bulk RTIL interfaces in contact with air and silver metal surfaces. Thin films are introduced by a highly controlled dynamic wetting process. Bulk interfaces are prepared by immersing the metal electrode into an IL solution. Data from ellipsometry, vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The static and dynamic structures of thin films of AILs adjacent to various substrates including mica, silica, silver, , Au(111), , Ni(111), Pd(111), , and Al 2 O 3 /NiAl­(110) have been reported. The structure present was characterized using many surface-specific techniques and some vacuum based-techniques, for example, reflection–absorption infrared (RAIRS) or angle resolved XPS spectroscopy, spectra of the latter made possible due to low IL vapor pressures…”
Section: The Structure Of the Solid–ionic Liquid Interfacementioning
confidence: 99%
“…The static and dynamic structures of thin films of AILs adjacent to various substrates including mica, silica, silver, , Au(111), , Ni(111), Pd(111), , and Al 2 O 3 /NiAl­(110) have been reported. The structure present was characterized using many surface-specific techniques and some vacuum based-techniques, for example, reflection–absorption infrared (RAIRS) or angle resolved XPS spectroscopy, spectra of the latter made possible due to low IL vapor pressures…”
Section: The Structure Of the Solid–ionic Liquid Interfacementioning
confidence: 99%
“…Finally, previous work from our group has shown that the substrates are sufficiently smooth to treat the boundary layer as static. , Some ILs are non-Newtonian fluids and are not necessarily expected to follow the Landau–Levich model. Their physicochemical properties that lead to deviations from this model are fundamentally interesting. ,,, The work presented here aims to determine how mixing ILs with traditional Newtonian molecular solvents, e.g., water and acetonitrile, affects these physicochemical behaviors. We are particularly interested in the thin film structure as it includes the “interfacial” and “bulk” phases and the dynamics of the IL system converting between these two phases. …”
Section: Resultsmentioning
confidence: 99%
“…Their physicochemical properties that lead to deviations from this model are fundamentally interesting. 39 , 42 , 43 , 47 49 The work presented here aims to determine how mixing ILs with traditional Newtonian molecular solvents, e.g., water and acetonitrile, affects these physicochemical behaviors. We are particularly interested in the thin film structure as it includes the “interfacial” and “bulk” phases and the dynamics of the IL system converting between these two phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation